Keperluan, kepentingan dan sumbangan perancangan pendidikan dalam pembangunan ekonomi Malaysia - Hasnah Ali,; Luqman Ahmad,; Sanep Ahmad,; Noraziah Ali, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2009)
For most developing countries positive growth rates should be maintained in order to make sure that all the development plans could be implemented successfully. Malaysia is able to sustain the economic growth due to the well planning system of the country. The development planning of the country started with the First Outline Perspective Plan (OPP 1) until the Third Outline Perspective Plan (OPP 3) which encompass the main national development policies such as the New Economic Policy (DEB), National Development Policy (DPN) and National Vision Policy (DWN). To date all the policies as itemized in the five year development plans have succeeded in maintaining the growth rates of the country. After the formation of Malaysia in 1963, the education structure has changed whereby the education planning is associated with strengthening the national education system and building social, economic and political unity. Before 1970 majority of the bumiputras were weak in their educational level, leaving only very few to be able to enter the more professional jobs. Education and human resource development is the key to increasing the country’s competitiveness. This paper analyzed the importance of education in the development planning of the education sector and empirical study was also done to show its contribution towards Gross Domestic Product (GDP). It was found that in each of the Malaysia Plan starting from the First Malaysia Plan up to the current Malaysia Plan, the aspect of education and human resource development has always been emphasized. The human resource development policy especially the education and training sectors have grown in great importance with the shift in the Malaysian economy from capital intensive to labor intensive and to the more technology intensive economy. A high proportion of the government expenditure is allocated to the education sector and this has contributed some positive effects in reducing poverty and the restructuring of the Malaysian societies to upheld the DEB, DPN and DWN